Triple-cell lineage tracing by a dual reporter on a single allele - Liu, Kuo (J Biol Chem, 2020)
Genetic lineage tracing is widely used to study organ development and tissue regeneration. Multicolor reporters are a powerful platform for simultaneously tracking discrete cell populations. Here, combining Dre-rox and Cre-loxP systems, we generated a new dual-recombinase reporter system, called Rosa26 traffic light reporter (R26-TLR), to monitor red, green, and yellow fluorescence. Using this new reporter system with the three distinct fluorescent reporters combined on one allele, we found that the readouts of the two recombinases Cre and Dre simultaneously reflect Cre(+)Dre(−), Cre(−)Dre(+), and Cre(+)Dre(+) cell lineages. As proof of principle, we show specific labeling in three distinct progenitor/stem cell populations, including club cells, AT2 cells, and bronchoalveolar stem cells, in Sftpc-DreER;Scgb1a1-CreER;R26-TLR mice. By using this new dual-recombinase reporter system, we simultaneously traced the cell fate of these three distinct cell populations during lung repair and regeneration, providing a more comprehensive picture of stem cell function in distal airway repair and regeneration. We propose that this new reporter system will advance developmental and regenerative research by facilitating a more sophisticated genetic approach to studying in vivo cell fate plasticity.